First detection and molecular characterization of porcine reproductive and respiratory syndrome virus in Namibia, Africa - Molini, Umberto; Coetzee, Lauren M.; Hemberger, Maria Y.; Chiwome, Bernard; Khaiseb, Siegfried; Dundon, William G.; Franzo, Giovanni (Frontiers in Veterinary Science, 2024)
Introduction The swine sector in Africa plays an important role in local economies, contributing to poverty alleviation and community subsistence. In addition, intensive farming is progressively becoming more important in the region. Therefore, any disease affecting swine populations can have detrimental effects on local communities. Porcine Reproductive and Respiratory Syndrome (PRRS) is among the most important infectious diseases affecting swine worldwide, but information on its epidemiology in Africa is extremely limited. Material and methods In the present study, 147 healthy butchered pigs, originating from 15 Namibian intensive and rural farms were tested by RT-PCR and the ORF7 genes of positive samples were sequenced for further genetic characterization and phylogenetic analysis. Additionally, 55 warthogs were also evaluated using the same approach. Results Overall, 7 out of 147 pigs (4.76%) tested positive, all originating from 3 rural farms (with a within-herd detection frequency higher than 14%) characterized by strong epidemiological links. All industrial pig and warthog samples were negative. Sequence analysis revealed that all strains belonged to the Betaarterivirus suid1 species, previously known as PRRSV type I, and were likely imported from Europe at least 6 years ago, evolving independently thereafter. When and how the first introduction occurred could not be determined due to the absence of other African sequences for comparison. Discussion The present work provides the first detection and characterization of PRRSV molecular epidemiology in Namibia. Based on the present findings, the presence of the PPRSV appears marginal and limited to backyard farms. While biosecurity measures applied in industrial farms appear to be effective in preventing viral introduction, PRRSV circulation in rural settings still represents a potential threat, and considering the socio-economical implication of livestock diseases decreasing animal performances in rural areas, active monitoring should be encouraged to promptly act against emerging menaces and guarantee the welfare of local pig populations.